Critical Review of The Psychology of Money by Morgan Housel: A Behavioral Perspective on Financial Decision-Making - Teguh Setiawan (Jurnal Keuangan dan Perbankan, 2025)
This article presents a critical review of Morgan Housel’s bestselling book, "The Psychology of Money", through the lens of behavioral finance. Housel argues that financial outcomes are driven more by human behavior and psychological factors than by technical knowledge or intelligence. The review evaluates key themes in the book—such as risk, luck, greed, patience, compounding, and the emotional dimensions of money-while linking them to foundational theories in behavioral economics by scholars like Kahneman, Tversky, Thaler, and Shefrin. Although the book lacks formal empirical methodology, its narrative-driven approach effectively communicates complex financial ideas to a broad audience. The review also highlights the pedagogical value of the book and its relevance to personal finance education. Limitations regarding academic rigor and global applicability are discussed. Overall, the review underscores the importance of incorporating behavioral perspectives into financial decision-making.